I started learning QED and I'm making my way through some introductory literature. I encountered a problem in a section that derives the commutator between the fields, $\left[A_i(x);E^j(y) \right] $. Working in the Coulomb gauge, they quote a naive guess:

$$\left[A_i(\vec x),E^j(\vec y) \right] = i\delta^j_i\delta(\vec x-\vec y)$$

But then go on to argue that we want $\nabla\cdot \vec{A} = \nabla \cdot \vec{E} = 0$ to hold, so should definitely have:

$$\left(\nabla\cdot \vec{A} \right) \left(\nabla \cdot \vec{E}\right) - \left(\nabla \cdot \vec{E}\right) \left(\nabla\cdot \vec{A} \right) = \left[\nabla\cdot \vec{A} , \nabla \cdot \vec{E} \right] = 0$$

but then using the naive commutator we get

$$\left[\nabla\cdot \vec{A}(\vec x) , \nabla \cdot \vec{E}(\vec y) \right] = i\nabla^2\delta(\vec{x}-\vec{y}) \neq 0$$

Now, I don't quite see how the last equality holds. I am not sure what to do with the differential operators in my commutator. Normally I'd try something along the lines of:

$$[\partial_x \phi(x),\psi(y)] = \partial_x[\phi(x),\psi(y)] + [\partial_x,\psi(y)]\phi(x) = \partial_x[\phi(x),\psi(y)] + 0$$

Where the second term vanishes as all derivatives are in $x$. But if I try to do a similar thing here I get something like:

$$\left[\nabla\cdot \vec{A}(\vec x) , \nabla \cdot \vec{E}(\vec y) \right]=\nabla\cdot\left[ \vec{A}(\vec x) , \nabla \cdot \vec{E}(\vec y) \right] =\nabla_y\cdot \left(\nabla_x \cdot\left[ \vec{A}(\vec x) , \vec{E}(\vec y) \right]\right) $$ (I put the subscripts in the last line so it;s clear which operator acts on which variable)

And clearly something goes wrong when I try to pull out the second divergence operator. Where am I going wrong with this? Thanks for your time!


1 Answer 1


If you are to have $$ \left[A_i(\vec x),\,E^j(\vec y) \right] = i\delta^j_i\delta(\vec x-\vec y) $$ and $\nabla\cdot A=\nabla\cdot E=0$, then you must also have $$ \begin{aligned} i\nabla_x^j\delta(\vec x-\vec y)&=i\nabla^i_x\delta_i^j\delta(\vec x-\vec y) \\&=\nabla^i_x\left[A_i(\vec x),\,E^j(\vec y) \right] \\&=\left[\nabla^i_xA_i(\vec x),\,E^j(\vec y) \right] \\&=\left[0,\,E^j(\vec y) \right] \\&=0 \end{aligned} $$ a contradiction.

The only "non-trivial" step in the manipulation above is $\nabla^i_x\left[A_i(\vec x),\,E^j(\vec y) \right]=\left[\nabla^i_xA_i(\vec x),\,E^j(\vec y) \right]$. Convince yourself that it is a correct manipulation (because the $\nabla_x$ only acts on functions of $x$, as indicated by the subscript).

Note that for this argument, we only used $\nabla\cdot A=0$. We didn't even need to use the second condition, $\nabla\cdot E=0$, to arrive at a contradiction.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.